2015
DOI: 10.1186/1476-069x-14-6
|View full text |Cite
|
Sign up to set email alerts
|

Drinking well water and occupational exposure to Herbicides is associated with chronic kidney disease, in Padavi-Sripura, Sri Lanka

Abstract: BackgroundThe chronic kidney disease of unknown etiology (CKDu) among paddy farmers in was first reported in 1994 and has now become most important public health issue in dry zone of Sri Lanka. The objective was to identify risk factors associated with the epidemic in an area with high prevalence.MethodsA case control study was carried out in Padavi-Sripura hospital in Trincomalee district. CKDu patients were defined using health ministry criteria. All confirmed cases (N = 125) fulfilling the entry criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
177
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 30 publications
6
177
1
7
Order By: Relevance
“…The study did not specify exactly to which pesticides the children were exposed, but glyphosate is a general-purpose herbicide whose use in rice paddies in Sri Lanka led to widespread kidney failure among young agricultural workers there, ultimately resulting in a ban on glyphosate usage in Sri Lanka [4,5]. While glyphosate is technically an organophosphonate rather than an organophosphate, a study on the fish Prochilodus lineatus has demonstrated that it suppresses cholinesterase in both muscle and brain [39].…”
Section: Evidence Of Dna Damage From the Research Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The study did not specify exactly to which pesticides the children were exposed, but glyphosate is a general-purpose herbicide whose use in rice paddies in Sri Lanka led to widespread kidney failure among young agricultural workers there, ultimately resulting in a ban on glyphosate usage in Sri Lanka [4,5]. While glyphosate is technically an organophosphonate rather than an organophosphate, a study on the fish Prochilodus lineatus has demonstrated that it suppresses cholinesterase in both muscle and brain [39].…”
Section: Evidence Of Dna Damage From the Research Literaturementioning
confidence: 99%
“…agricultural workers in the northern region [4,5], and was probably further motivated by the WHO reevaluation of its carcinogenic potential. Kidney disease is a risk factor for multiple cancers, with kidney dialysis being associated with increased risk of Kaposi's sarcoma by more than 50-fold, with 3-to 10-fold increased risk of kidney cancer, and 2-to 9-fold increased risk of thyroid cancer.…”
Section: R Pmentioning
confidence: 99%
“…Male farmers from North-Central province (NCP) who spray glyphosate-based herbicides, drink water from shallow wells and had history of drinking from an abandoned Faculty of Medicine and Allied Sciences, Rajarata University of Sri Lanka, Saliyapura, Anuradhapura 50008, Sri Lanka well (abandoned due to increasing foul taste), are at higher risk of developing CINAC [2]. Chronic low dose exposure to multiple heavy metals and agrochemicals is hypothesized as the etiological factor for CINAC [3].…”
Section: Introductionmentioning
confidence: 99%
“…Those crystals may injure the kidneys. However, other causal factors have been debated, such as metals and silica in the drinking water or pesticides used in farming (4,5). It is possible that the disease is multifactorial, depending on the region.…”
mentioning
confidence: 99%